Pengaruh Kepemimpinan dan Disiplin Kerja terhadap Kinerja Karyawan Apotek Libra Surabaya - Venia Dwi Wardani; Iswati Iswati; Siti Aisah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In This research aims to determine the influence of leadership and work discipline on employee performance at Libra Pharmacy Surabaya. This research uses quantitative research methods. The sample used was all employees who worked at Libra Pharmacy Surabaya, totaling 32 employees. Data collection techniques used questionnaires. The research variables are the independent variable leadership performance and discipline, the dependent variable is employee performance. Mei-Juni 2024. Libra pharmacy employees. The results of this research are that leadership has a significant effect on the performance of Libra pharmacy employees. The conclusion obtained from the results of the regression equation analysis is that the regression coefficient value for leadership is -1.072 with a negative relationship direction, which means that if leadership is increased, employee performance will be lower and vice versa, if leadership is low then the level of employee performance will be higher. Apart from that, it has a calculated t value of -3.481 < t table 1.699 and has a probability value of 0.002 < 0.05, then H is accepted. Work discipline has a significant effect on the performance of Libra pharmacy employees. The conclusion obtained is that from the results of the regression equation analysis, the regression coefficient value for work discipline is -0.907 with a negative relationship direction, which means that if work discipline is increased, employee performance will be lower and vice versa, if work discipline is low then the level of employee performance will be higher. high., apart from that it has a calculated t value of -5.447 < t table 1.699 and has a probability value of 0.000 < 0.05, then H is accepted.